Didactization of a youth novel as CALL material for advanced Grade 11– 12 learners of German as a foreign language - Strack, Uwe-Michael Peter Bernhard (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Modern Foreign Languages))--University of Stellenbosch, 2006.